Advancing Primary Care Use of Electronic Medical Records in Canada - Jennifer Zelmer; Simon Hagens (McMaster University Library Press, 2014)
In 2010, the federal government's Economic Action Plan funded Canada Health Infoway to co-invest with provinces, territories, and health care providers in electronic medical records (EMRs) in primary care. The goal is to help improve access to care, quality of health services, and productivity of the health system, as well as to deliver economic benefits. The decision to fund EMRs was consistent with a long-term framework for digital health established in consultation with stakeholders across the country, spurred by analysis demonstrating the economic impact of such investments and data on Canada's low rate of EMR use in primary care compared with other countries. The decision reflected widespread public and stakeholder consensus regarding the importance of such investments. EMR adoption has more than doubled since 2006, with evaluations identifying efficiency and patient care benefits (e.g., reduced time managing laboratory test results and fewer adverse drug events) in community-based practices. These benefits are expected to rise further as EMR adoption continues to grow and practices gain more experience with their use.